(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article explores the pedagogical conditions necessary for effectively organizing student activities through ethnopedagogical models. It emphasizes the significance of integrating cultural context into educational practices, fostering student engagement and enhancing learning outcomes. By examining various ethnopedagogical approaches, the article aims to provide educators with practical strategies to enrich student experiences and promote cultural awareness.